2019
DOI: 10.1039/c9fo00333a
|View full text |Cite
|
Sign up to set email alerts
|

A Mediterranean diet does not alter plasma trimethylamineN-oxide concentrations in healthy adults at risk for colon cancer

Abstract: A Mediterranean diet does not reduce circulating TMAO, a metabolite that is associated with chronic disease risks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(50 citation statements)
references
References 52 publications
1
43
0
Order By: Relevance
“…We focused the report on 27 articles as shown in the PRIMA diagram [ 25 - 51 ]; 13 of these studies were carried out in Spain [ 26 - 28 , 33 , 35 , 38 , 41 , 44 - 46, 48, 49, 51 ], 3 studies were carried out in the USA [ 25 , 31 , 47 ], 3 studies were carried out in Italy [ 30 , 36 , 40 ], 4 studies were carried out in other European Union countries [ 32 , 34 , 39 , 50 ] and 4 studies were carried out in Australia [ 29 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…We focused the report on 27 articles as shown in the PRIMA diagram [ 25 - 51 ]; 13 of these studies were carried out in Spain [ 26 - 28 , 33 , 35 , 38 , 41 , 44 - 46, 48, 49, 51 ], 3 studies were carried out in the USA [ 25 , 31 , 47 ], 3 studies were carried out in Italy [ 30 , 36 , 40 ], 4 studies were carried out in other European Union countries [ 32 , 34 , 39 , 50 ] and 4 studies were carried out in Australia [ 29 , 37 , 42 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a paleolithic diet rich in whole grains also led to lower serum TMAO and abundance of TMA producer Hungatella [130]. In 115 healthy people at increased risk of developing colon cancer, a Mediterranean (moderate in fish) diet did not cause significant changes in the (fasting) TMAO concentrations after 6 months of supplementation [131]. Daily red meat consumption (providing 258 mg L-carnitine/day) [95] caused elevations in TMAO median levels of around 7 µM (interquartile range 4-11 µM).…”
Section: Tmao Variability By Dietmentioning
confidence: 97%
“…Dysbiosis has been shown to promote kidney disease, since the intestinal barrier becomes more permeable for microbially generated metabolites [145][146][147]. Relative abundance of Akkermansiamucinophilia in colon biopsies was shown to be inversely correlated with TMAO levels [131]. A. mucinophilia is a mucotroph bacterium and an indicator of a functioning intestinal mucus layer [126,148].…”
Section: Tmao Variability By Microbiome Variabilitymentioning
confidence: 99%
“…Epidemiological studies have reported an inverse correlation between habitual adherence to the Mediterranean diet and urinary [ 156 ] as well as plasma [ 157 ] TMAO levels in the Southern European population. However, six months of Mediterranean dietary intervention failed to reduce the fasting TMAO concentration in healthy North American volunteers at risk of colon cancer [ 158 ]. This discrepancy may be explained by population differences, which are known to affect the microbiota composition [ 159 ].…”
Section: Potential Therapies In Choline-related Diseasesmentioning
confidence: 99%